The talisman of good fortune and other stories from rural Bhutan - Rinzin, Rinzin (Thimphu : Kuensel Corporation, 2002)
The Talisman of Good Fortune and Other Stories from Rural Bhutan is a collection of nine fictitious short stories based on rural Bhutanese culture, beliefs and norms. The stories take the reader through some of the most simple beliefs, and lives, of the lay Buddhist rural Bhutanese in particular, and most Bhutanese in general, to the most complex and eerie but equally fascinating world of The Poison Givers, Persons with the Evil Spirit of the Living, Persons who cast Evil Spells, and what the author calls 'The Clandestine Foes.' The stories provide the reader a good insight of the 'least known' (to the outside world) and the 'least written' side of the rural Bhutanese life. Furthermore, the stories are highly thought provoking.